The TH1902 Docetaxel Peptide-Drug Conjugate Inhibits Xenografts Growth of Human SORT1-Positive Ovarian and Triple-Negative Breast Cancer Stem-like Cells - Michel Demeule; Cyndia Charfi; Jean-Christophe Currie; Alain Zgheib; Bogdan Alexandru Danalache; Richard Béliveau; Christian Marsolais; Borhane Annabi (MDPI AG, 2022)
Background: Breast and ovarian cancer stem cells (CSC) can contribute to the invasive and chemoresistance phenotype of tumors. TH1902, a newly developed sortilin (SORT1)-targeted peptide-docetaxel conjugate is currently in phase-1 clinical trial. Whether TH1902 impacts the chemoresistance phenotype of human triple-negative breast CSC (hTNBCSC) and ovarian CSC (hOvCSC) is unknown. Methods and Results: Immunophenotyping of hTNBCSC and hOvCSC was performed by flow cytometry and confirmed the expression of SORT1, and of CSC markers CD133, NANOG, and SOX2. Western blotting demonstrated the expression of the drug efflux pumps from the P-gp family members, ABCB1 and ABCB5. The cellular uptake of the fluorescent Alexa488-peptide from TH1902 was inhibited upon siRNA-mediated repression of SORT1 or upon competition with SORT1 ligands. In contrast to docetaxel, TH1902 inhibited in vitro migration, induced cell apoptosis and lead to G2/M cell cycle arrest of the hTNBCSC. These events were unaffected by the presence of the P-gp inhibitors cyclosporine A or PSC-833. In vivo, using immunosuppressed nude mice xenografts, TH1902 significantly inhibited the growth of hTNBCSC and hOvCSC xenografts (~80% vs. ~35% for docetaxel) when administered weekly as intravenous bolus for three cycles at 15 mg/kg, a dose equivalent to the maximal tolerated dose of docetaxel. Therapeutic efficacy was further observed when carboplatin was combined to TH1902. Conclusions: Overall, TH1902 exerts a superior anticancer activity than the unconjugated docetaxel, in part, by circumventing the CSC drug resistance phenotype that could potentially reduce cancer recurrence attributable to CSC.